The vitality of the earthworm developing in soil treated with different concentrations of leaves and fruits powders of Melia azaderach L - Safaa Mahmoud; Adnan Mohammed (College of Education for Pure Sciences, 2018)
The present study investigated the effect of five concentrations (1,2.5,5,7.5,10%) of leaves and fruits of Melia azaderach L . plant powder on relative growth rate of earthworm after one and two months post treatment , the results revealed that the relative growth rate was decreased and the least one was the concentration at 7.5% for leaves and fruits powder of Melia azaderach L. plant,of 44.4%and71.55%, respectively. In addition , the effect of these concentrations on increasing and decreasing worms weights was studied and showed that all concentrations led to weight decrease of in treated worms especially at the concentration 7.5% during two breeding period , also noticed that during a second period of Treatment with leaves powder at 5,7.5, 10% concentrations during the second breeding period led to worms death and incomplete life cycle.Death. Furthermore, the percentage of death was estimated at the same concentrations of leaves and fruits powder during two breeding periods, in additon to the effect of these concentrations on protein content in worm bodies, the thickness of body wall (epidermis and body wall )was estimated in addition to the thickness of the epithelial layer of digestive tract, and the effect on the internal structures in treated worms.